Gypsies and travellers : empowerment and inclusion in British society / edited by Joanna Richardson and Andrew Ryder. - Richardson, Joanna, 1972 June 5-; Ryder, Andrew (Andrew Richard) (Policy, 2012)
This topical book examines and debates a range of themes facing gypsies and travellers in British society, including health, social policy, employment and education.